2019
DOI: 10.26434/chemrxiv.7695224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigations of Thermally-Controlled Mechanochemical Milling Reactions

Abstract: Mechanochemical milling reactions gained a lot of attention lately as a green and highly efficient path towards various relevant materials. The control over the fundamental reaction parameters in milling procedure, such as temperature and pressure of the reactor, is still in infancy and the vast majority of milling reactions is done with controlling just the basic parameters such as frequency and milling media weight. We demonstrate here how the milling under controlled, prolonged and variable heating programs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…In this regard, in the past few years, various synthetic techniques such as direct mechanocatalysis [21][22][23][24][25] and liquid assisted grinding [26][27][28][29][30][31] are developed. New possibilities for heating [32][33][34] , cooling 35,36 and conducting gaseous 37,38 mechanochemical reactions are established. Furthermore, analytical techniques for in situ monitoring of the reactions are described [39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…In this regard, in the past few years, various synthetic techniques such as direct mechanocatalysis [21][22][23][24][25] and liquid assisted grinding [26][27][28][29][30][31] are developed. New possibilities for heating [32][33][34] , cooling 35,36 and conducting gaseous 37,38 mechanochemical reactions are established. Furthermore, analytical techniques for in situ monitoring of the reactions are described [39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…Additionally, to study the effect of the temperature on the peptide bond formation, we applied a recently described temperature-controlled ball milling protocol. 45 For example, in a standard experiment, Gly (60 mg, 0.80 mmol) was milled with a five-fold molar excess of TiO2 (anatase), at 30 Hz for 18 h and temperatures ranging from room temperature to 130 °C, thus respecting practical thermal limits for prebiotic peptide bond formation, 18,19 while acknowledging the expected dilution of amino acids on mineral surfaces under prebiotic conditions (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…3), who demonstrated that the major chemical product of the reaction between para-phenylenediamine (PDA) and para-nitrobenzoyl azide (PNBA) could be altered through control of the reaction temperature using a water-heated milling reactor. 50 If the reaction was run at elevated temperatures such as 80 1C, the resulting product featured urea-linkages while at lower temperatures, the generation of connecting amide bonds predominated. These results emphasized the potential of controlling the vessel temperature with the goal of directing the mechanochemical reaction towards the desired product.…”
Section: Guide To Direct Mechanocatalysispart 1: Milling Parametersmentioning
confidence: 99%
“…3 Reaction between PDA and PNBA at different temperatures investigated by Uz ˇarevic ´group. 50 of the reaction vessel, the use of coolants such as liquid nitrogen during mechanochemical reactions is referred to as ''cryo milling''. 39 However, these conditions are not well suited for organic synthesis in the ball mill and few reports for the use of cryo milling in organic synthesis are available.…”
Section: Guide To Direct Mechanocatalysispart 1: Milling Parametersmentioning
confidence: 99%